Effect of vanadium and silver nanoparticles on the structural, DC conductivity, and optical properties of erbium-doped borate glass / Nur Adyani Zaini - Zaini, Nur Adyani (2023)
In this study, two series of borate glass with composition (59.5–x)B2O3–20Na2O–20CaO–xV2O5–Er2O3–0.5AgCl (x = 0, 0.5, 1.0, 1.5, 2.0, and 2.5 mol%) and (57.5–y)B2O3–20Na2O–20CaO–1.5V2O5–1Er2O3–yAgCl (y = 0, 0.3, 0.5, and 1.0 mol%) have been successfully prepared by conventional melt quenching method. Structural investigation of glass samples was determined by X-Ray diffraction (XRD), Transmission Electron Microscopy (TEM), and Fourier Transform Infrared (FTIR). The direct current (DC) conductivity was carried out by Electrochemical Impedance Spectroscopy (EIS). In addition, the optical properties of the glass samples were recorded by UV–Vis–NIR spectrometer and Photoluminescent Spectroscopy (PL), respectively. The increase of V2O5 concentration in ErO3 doped B2O3–Na2O–CaO embedded with silver nanoparticle glasses caused the increment of density from 2.494 to 2.521 g/cm3 and molar volume from 2.79 to 2.87 cm3. This result indicated the replacement of light and short bonds of B2O3 with a heavy and long bond of V2O5, which cause the change in the glass structure. The FTIR confirmed the presence of BO3, BO4, VO4, and VO5 vibration groups. In this glass series, FTIR spectra revealed that the V2O5 act as a modifier at low concentration (x ≤ 1.0 mol%) and act as former glass at high concentration (x > 1.0 mol%). The minimum direct current (DC) conductivity at x = 1.0 mol% was suggested due to the blocking of Na+ and Ca+ in mixed ionic electronic (MIE) glass. Surprisingly, the intensity of absorption transition 2H11/2 showed an increase as the addition of V2O5 except at x = 1.0 mol%, indicating a possible due to MIE impact on the intensity of absorption. Moreover, with the addition of V2O5 in the glass samples, the energy band gap decreased from 3.143 eV to 2.422 eV. Meanwhile, the refractive index increased from 2.3596 to 2.5731. However, the anomalous region was plotted at x = 1.0 mol%, coinciding with minimum DC conductivity. Hence, the MIE effect influences the optical properties of the glass samples. The Judd–Ofelt parameter showed an off trend within a similar region due to the MIE effect. The emission intensity increased by adding ≤ 1.5 mol% and decreased when further addition of V2O5. This reduction was suggested due to the quenching effect. For (57.5–y)B2O3–20Na2O–20CaO–1.5V2O5–1Er2O3–yAgCl, The bridging oxide (BO) and non-bridging oxide (NBO) were detected by structural analysis. The UV–vis–NIR absorption spectra revealed eight bands at 450, 489, 520, 539, 664, 800, 987, and 1556 nm without the addition of new bands which correspond to the surface plasmon resonance (SPR) band. However, the TEM images confirmed the presence of Ag nanoparticles (NPs). The DC conductivity with Ag NPs increased to a maximum value at y = 0.5 mol%, signifying a smooth movement of Na+ and Ca+ in the MIE glass. In optical analysis, the energy bandgap showed a reciprocal behavior to the refractive index and Urbach energy. The energy bandgap showed a maximum point at y = 0.5 mol%; meanwhile, the refractive index, and Urbach energy showed a minimum point at y = 0.5 mol%, which coincided with maximum DC conductivity. In addition, the Judd–Ofelt parameter showed a slope change at y = 0.5 mol%, which indicates the MIE effect impacts the Judd–Ofelt parameter. The emission spectra under excitation at 800 nm showed three dominant peaks at 506 nm, 548 nm, and 635 nm. The intensity of luminesce range increased as the concentration of Ag NPs increased. Based on the PL results, these series of glass samples were beneficial in green laser application since they have the highest intensity in the green emission region.